Solastalgia : A comparative corpus-based study of environmental lexicon - Lucia Abbamonte; Bronwen Hughes (Russian Journal of Linguistics)
This study focuses on the evolving environmentally related lexicon and the new meanings that have progressively arisen or born of the combination of pre-existing terms and lemmas. The increasingly widespread practice among news professionals, psychologists, sociologists etc. of listening, recording and collecting narratives centred upon environmental alterations has enhanced the tendency to coin new words. Neologisms, such as eco-grief, eco-anxiety, solastalgia, are progressively entering mainstream communication, though due to its more complex morphological makeup the term ‘solastalgia’ requires more in-depth analysis. The objective of the present study is to investigate the early use of the term solastalgia in scientific communication and trace its subsequent development and transition to mainstream communication. The progressive shift was investigated through an integrated methodological approach, based on a comparative corpus-based analysis (time span 2007-2023), and further informed by an ecolinguistics perspective. The data were obtained from two diachronic sub-corpora, specifically created for the purpose of this investigation: the Eco-PubMed corpus, extracted from the PubMed Central archive, and the Eco-Guardian corpus taken from the online international version of the Guardian newspaper. Both quantitative and qualitative aspects were taken into account, together with the cultural-pragmatic implications of this fast-emerging new locution. The results reveal that the term ‘solastalgia’ has only reached mainstream communication to a limited extent, since it occurs in 31 PubMed articles vs 17 Guardian articles. The diffusion of the term belied the authors’ expectations regarding the greater neutrality of scientific dissemination compared to mainstream communication. The study raises awareness of the dissemination of environment-related terminology and its interdisciplinary relationship to other domains.